Analysis of the Effect of Economic Growth and Foreign Direct Investment (FDI) on Employment in Maluku Province (Period 2000 – 2020) - Zulaiha Kapitanhitu, Siti; Sangadji, Maryam; Ramly, Fahrudin (PT Mattawang Mediatama Solution, 2024)
This study aims to determine the effect of economic growth and Foreign Direct Investment (FDI) on labor demand in Maluku Province. The data used is secondary data obtained from the Central Bureau of Statistics of Maluku Province from 2000-2020. The analysis method used is multiple liner rehression. The results showed that economic growth had a positive and significant effect on labor demand while FDI had a positive but not significant effect.